2020
DOI: 10.2147/ijn.s235815
|View full text |Cite
|
Sign up to set email alerts
|

<p>Encapsulated <em>n</em>-Butylidenephthalide Efficiently Crosses the Blood–Brain Barrier and Suppresses Growth of Glioblastoma</p>

Abstract: Background: n-Butylidenephthalide (BP) has anti-tumor effects on glioblastoma. However, the limitation of BP for clinical application is its unstable structure. A polycationic liposomal polyethylenimine (PEI) and polyethylene glycol (PEG) complex (LPPC) has been developed to encapsulate BP for drug structure protection. The purpose of this study was to investigate the anti-cancer effects of the BP/LPPC complex on glioblastoma in vitro and in vivo. Methods: DBTRG-05MG tumor bearing xenograft mice were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…PEG-coated NPs have strong ability to cross biological barriers, such as epithelial cells, and escape phagocytosis by immune cells. 23 As expected, delivery efficiency was aided by the expression of DiR ( Figure 1B ). Blocking ST2 may provide a new therapeutic strategy for patients with asthma.…”
Section: Discussionsupporting
confidence: 71%
“…PEG-coated NPs have strong ability to cross biological barriers, such as epithelial cells, and escape phagocytosis by immune cells. 23 As expected, delivery efficiency was aided by the expression of DiR ( Figure 1B ). Blocking ST2 may provide a new therapeutic strategy for patients with asthma.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, the prototype components and metabolites in the cerebrospinal fluid after oral administration of Qi-Fu-Yin have not been reported. Several research showed that some saponins in GRR [ 55 , 56 ], GRP [ 57 ], and phthalides in ASR [ 58 , 59 ] can be absorbed into the cerebrospinal fluid. In addition, saponins in GRR [ 60 ] and GRP [ 61 ], flavonoids in ZSS [ 62 ], and source esters in PRP [ 53 ] have been determined in the brain tissue homogenate.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we demonstrated the inhibitory effect of BP/LPPC on breast cancer in vitro, its detailed inhibitory effect and mechanisms in tumorbearing mice is a weakness in the present study. To supportive the anticancer activity of BP/LPPC in vivo, we would descript our previous study that revealed BP/LPPC suppressed GBM growth in xenograft and orthotopic animal model and, therefore, we assumed the same formulation of BP/LPPC was implied similar anti-cancer effects in breast cancer in vivo [36]. Furthermore, in our previous research, we utilized LPPC to encapsulate doxorubicin and randomly adsorbed Herceptin on the surface of LPPC.…”
Section: Discussionmentioning
confidence: 99%
“…Liposome complex containing PEI and PEG (Lipo-PEG-PEI complex, LPPC) encapsulation, a new type drug carrier, has been verified the encapsulation efficacy of LPPC on curcumin, doxorubicin, and BP in breast, colon, glioma, and melanoma cancer therapy in vitro and in vivo and suggests that LPPC could be used as an effective drug carrier for stabilizing the activity of drugs [28][29][30][31][32][33][34][35][36]. LPPC is composed of DOPC and DLPC, which are two natural lipids that can be metabolized by the liver.…”
Section: Introductionmentioning
confidence: 99%